CMAS corrosion-resistance micronanometer composite thermal barrier coating layer and preparation method thereof - WEI LIANGLIANG; GUO HONGBEI; DENG YANGPI (2016)
The invention discloses a preparation method of a CMAS corrosion-resistance micronanometer composite thermal barrier coating layer. The thermal barrier coating layer includes a bonding layer prepared on an alloy basal body, a first ceramic layer and a second ceramic layer; the first ceramic layer is a yttrium oxide part stable zirconium oxide coating layer, can be prepared by atmosphere plasma spraying, an electronic beam physical vapor deposition method or a plasma evaporation deposition method, and has a thickness of 50-200 microns; and the second ceramic layer is a CMAS-resistance coating layer prepared by a plasma evaporation deposition system, and has a thickness of 1-100 microns. At high temperature, molten CMAS is not wet on the surface of the prepared second ceramic layer. The prepared multi-layer thermal barrier coating layer system including the bonding layer, the first ceramic layer and the CMAS-resistance second ceramic layer can effectively stop permeation of molten CMAS, and is excellent in molt